Impact of specialty pharmacy collaboration with rheumatology clinics to improve the achievement of treat-to-target goals in patients with rheumatoid arthritis: a pilot study. Issue 2 (4th March 2023) - Ritenour, Alexandra; Yu, Anthony; Li, Diana; Martin, Tonya
Abstract: In rheumatoid arthritis, the use of Routine Assessment of Patient Index Data 3 (RAPID3) assessments to meet treat-to-target goals is endorsed by the 2021 American College of Rheumatology guidelines. In November 2020, the Baylor Scott & White specialty pharmacy implemented a new service that included more frequent collection of RAPID3 scores and standardized provider communication for patients co-managed by a Baylor Scott & White rheumatology clinic. The objective was to evaluate the impact of this new service on rheumatoid arthritis disease activity. Before the new service started, patients followed a protocol of RAPID3 assessments that occurred every 6 months; once the service began, patients were followed using an algorithm in which patients with higher disease activity were contacted more frequently. Eighty-six percent of patients in the pre-intervention group (n = 7) compared with 100% of patients in the post-intervention group (n = 10) had high to moderate disease activity at baseline. Within a 6-month follow-up period in both groups, the percentage of high to moderate disease activity patients decreased by 30% in the post-intervention group and remained the same in the pre-intervention group. These results support the positive impact increased specialty pharmacy services may have on clinical outcomes; therefore, the continued expansion of these services should be considered.